Woman without shame : poems - Cisneros, Sandra (Alfred A. Knopf, 2022)
"...Woman Without Shame is a moving collection of songs, elegies, and declarations that chronicle her pilgrimage toward rebirth and the recognition of her prerogative as a woman artist. These bluntly honest and often humorous meditations on memory, desire, and the essential nature of love blaze a path toward self-awareness. For Cisneros, Woman Without Shame is the culmination of her search for home--in the Mexico of her ancestors and in her own heart."--Dust jacket flap.